THE INFLUENCE OF PERCEPTION AND ATTITUDE ON MOTIVATION TO USE E-WALLET DURING THE COVID-19 PANDEMIC - Alif Fadlillah; Moh. Djemdjem Djamaludin (Journal of Child, Family, and Consumer Studies, 2023)
The existence of a new normal scenario during the COVID-19 pandemic causes changes in consumer behavior in utilizing the use of e-wallet as a substitute for cash in transactions, either in person or online. This study aims to analyze the effect of perceptions and attitudes on the motivation to use e-wallet for IPB students during the Covid-19 pandemic. This study uses an explanatory design involving 157 IPB University students using voluntary sampling technique. The results of the correlation test show that there is no significant relationship between the characteristics and the variables studied, perceptions and attitudes have a significant positive relationship with the motivation to use e-wallet during the Covid-19 pandemic. The results of the multiple linear regression test showed that the characteristics of the monthly allowance had a positive effect on motivation, then the perception and attitude variables had a significant positive effect on the motivation to use e-wallet. Suggestions for further research to be able to examine other variables or factors that can influence the motivation to use e-wallets. One of them is in terms of e-wallet risk and security.